Dissolution of commercial nanoscale silica particles in electrolyte solution: The importance of the solid-solvent-ratio to physical and chemical properties of the solid-liquid interface - Vogelsberger, Wolfram; Schmidt, Jochen (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2018)
Dissolution experiments of silica nanoparticles (NPs) were performed in an aqueous TRIS buffer system (pH = 7.6) at 25 degrees C and the effect of the particles to solvent ratio (PSR) was studied. Increasing the PSR distinctly promotes the kinetic size effect described previously, which leads to solute concentrations exceeding the thermodynamic saturation concentration under the respective conditions considerably. The striking experimental observations readily are rationalized by analysis of the Gibbs free energy (GFE) of the system. In the extended model approach the dissolution and Ostwald ripening is described using gradient curves of GFE, which have been calculated considering a variable interfacial tension of the solid-liquid-interface, gamma. The GFE analysis provides size, R-P, and concentration, Z(P), of NPs as a function of dissolution time. The variation of the interfacial tension with particle size, gamma(R-P), is a consequence of the properties of the electric double layer, surface charge and surface potential, around the NPs. Suggestions are made how to predict the dissolution process from properties of the initial system solid-solution. Any meaningful report of dissolution experiments should include the saturation concentration of the material that forms the NPs as thermodynamic criterion, and the time necessary to obtain half of the saturation concentration in the system considered as kinetic criterion. Both aforementioned criteria are accessible from experiments without any model considerations.
Keywords: Silica nanoparticle dissolution; Solid-solvent ratio; Kinetic size effect; Interfacial tension; Electrical double layer